Interactive effects of increased plant density, cultivars and N rates in environments with different cotton yield recovery potential - Galdi, Leonardo Vesco; Cordeiro, Carlos Felipe dos Santos [UNESP]; de Senna e Silva, Bruno; de La Torre, Elio Jesus Rodriguez; Echer, Fábio Rafael (Elsevier, 2022)
Nitrogen (N) is one of the most absorbed and exported nutrients by cotton plants (Gossypium hirsutum L.), but excessive rates can result in excessive growth and reduce fiber yield and quality. Combinations of high N rates and high plant density reduced yields, especially in locations where yield is higher than 2000 kg ha−1 of fiber. The effect on fiber quality (mainly micronaire and fiber strength) was lower in a location with the yield lower than 1600 kg ha−1 of fiber and higher where the yield is higher than 2000 kg ha−1 of fiber. Increasing the N rate is a strategy to boost yields with low soil fertility in low plant density crops and early maturation cultivars. The highest fiber yields were obtained with plant populations between 6.6 and 8.6 plants m−2 (66,000–86,000 plants ha−1) and the best N dose depends on the plant population. Proper management of plant density and N fertilization must consider the specific cultivar, yield environment, and cotton yield potential.
Keywords: Cotton fertilization; Nitrogen uptake; Yield components